2022
DOI: 10.1128/msystems.00282-22
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of Gut Microbiota and Intestinal Barrier Dysfunction in Pigs with Pulmonary Inflammation Induced by Mycoplasma hyorhinis Infection

Abstract: Cumulative evidence suggests that bacterial pneumonia may contribute to the dysbiosis of the gut microbiota and other gastrointestinal symptoms. Our experiment has demonstrated that lung inflammation induced by M. hyorhinis infection was associated with gut microbiota dysbiosis and intestinal barrier dysfunction, which may provide a theoretical basis for exploring the gut-lung axis based on M. hyorhinis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Alteration of the gut microbiota is related to intestinal permeability (Kang et al, 2022 ; Koutoukidis et al, 2022 ; Zhang et al, 2022 ). The intestinal barrier is key to blocking toxic substances and maintaining normal intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the gut microbiota is related to intestinal permeability (Kang et al, 2022 ; Koutoukidis et al, 2022 ; Zhang et al, 2022 ). The intestinal barrier is key to blocking toxic substances and maintaining normal intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by the results of a previous study: M. hyorhinis infection had a significant impact on the growth performance of pigs, as it resulted in a reduction in their average daily weight gain. 7 Genera with relative abundance wileyonlinelibrary.com/jsfa greater than 1% include Prevotella, Clostridium, Bacteroides, Ruminococcus, Oscillibacter, Roseburia, and Eubacterium. These genera are the most abundant and dominant bacteria in all pigs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Existing studies have reported that it is a common cause of pneumonia, polyarthritis, and arthritis, [4][5][6] and also can lead to growth retardation. 7 Moreover, M. hyorhinis usually coinfects with a variety of other pathogens in swine production. 8 The pathogenic mechanism of inflammatory diseases caused by M. hyorhinis infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota community is composed of a specific ratio of various bacterial species, in which species alternately restrict each other’s function and depend on each other to create an ecological balance. An imbalance in the microbiota community causes gut dysbiosis, which contributes to the development of diseases in pigs, including respiratory infection ( 73 ), postweaning diarrhea ( 74 ), impairment of the gut–liver axis ( 75 ), and intestinal barrier dysfunction ( 76 ). The fact that DF can alter microbiota composition indicates that the gut microbiota can be manipulated by DF as a way of improving the health of pigs.…”
Section: Df-microbiota Interaction and Intestinal Healthmentioning
confidence: 99%